2006
DOI: 10.1152/ajpregu.00235.2006
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cerebrospinal fluid transport across the cribriform plate into lymphatics in rats

Abstract: A major pathway by which cerebrospinal fluid (CSF) is removed from the cranium is transport through the cribriform plate in association with the olfactory nerves. CSF is then absorbed into lymphatics located in the submucosa of the olfactory epithelium (olfactory turbinates). In an attempt to provide a quantitative measure of this transport,125I-human serum albumin (HSA) was injected into the lateral ventricles of adult Fisher 344 rats. The animals were killed at 10, 20, 30, 40, and 60 min after injection, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 43 publications
0
65
0
Order By: Relevance
“…beyond the basal cisterns and CMJ. [21][22][23] Those CSF absorption devices declined possibly due to lengthy intracranial hypertension, especially in the patient with CSF diversion. 17,20,24 In other words, the previous ETV-treated OHCP might already coexist with "communicating HCP" due to the decrease in CSF absorption even before initial ETV.…”
Section: Discussionmentioning
confidence: 99%
“…beyond the basal cisterns and CMJ. [21][22][23] Those CSF absorption devices declined possibly due to lengthy intracranial hypertension, especially in the patient with CSF diversion. 17,20,24 In other words, the previous ETV-treated OHCP might already coexist with "communicating HCP" due to the decrease in CSF absorption even before initial ETV.…”
Section: Discussionmentioning
confidence: 99%
“…Such uptake would confound the ventricular PET signal. For this reason, 11 C-PiB, which shows binding in the nasal turbinates, was not used to estimate turbinate clearance. On the other hand, 11 C-cocaine, which does not show cortical or turbinate binding, was valuable as a validator.…”
Section: Csf Egress In Admentioning
confidence: 99%
“…In rodents and other mammals, CSF is primarily cleared along olfactory nerves that traverse the cribriform plate, draining into lymphatic vessels in the nasal mucosa (7)(8)(9)(10). Rodent CSF clearance is rapid because radiolabeled albumin (11), Indian ink (7), and paramagnetic contrast (10) injected into the CSF reach the turbinates within minutes. Much less is known about human CSF clearance anatomy.…”
mentioning
confidence: 99%
“…This system contributes to clearance of small molecules and proteins from interstitial fluid to lymph nodes in the neck and spine, and Johnston and colleagues have shown that it accounts for a large fraction of CSF clearance. [103][104][105][106] Early studies established rapid distribution of tracers inserted into interstitial fluid or CSF throughout the entire brain via perivascular fluid, and rates of tracer delivery to lymph nodes varied with head position, intracranial pressure, arterial pulsations, and other factors. 107,108 Amyloid-beta, 14 C-metabolites of [ 14 C]glucose, and fluorescent tracers are cleared via this pathway by mechanisms involving astrocytic water movements mediated by aquaporins.…”
Section: Some Speculations: Hypoglycemic Glycogenolysis Mitochondriamentioning
confidence: 99%